Challenges in interpretation of WGS and epidemiological data to investigate nosocomial transmission of vancomycin-resistant Enterococcus faecium in an endemic region: incorporation of patient movement network and admission screening - Eichel, Vanessa; Klein, Sabrina; Bootsveld, Carolin; Frank, Uwe; Heeg, Klaus; Boutin, Sébastien; Nurjadi, Dennis (The journal of antimicrobial chemotherapy, 2020)
AbstractObjectives. VRE are listed, by the WHO, among the leading resistant pathogens causing greatest public concern; hence the spread and transmission of VRE
Gesehen am 09.09.2020